Self-regulated learning profile of students with auditory learning style in mathematics lessons - Elly's Mersina Mursidik; Toto Nusantara; Abdur Rahman As'ari; Makbul Muksar (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2024)
Education aims to develop potential and make students more independent. Independent learning (Self-Regulated Learning) in mathematics learning needs to be built according to students' learning styles. Teacher instructions play an important role in triggering students to want to learn without being forced or forced so that students can be comfortable in learning mathematics. Qualitative case study research on the uniqueness of grade 7 male students with an auditory learning style at boarding schools is different from the theory that female students' SRL is better than male students. Of the 8 students with an auditory learning style, 1 student has a different uniqueness. Data collection used MIR (Multi Intelligence Research) documents, SRL inventory, direct observation, and interviews. As a result, teachers give students confidence in taking initiative and maintaining consistent intentions to learn mathematics. Students take advantage of the teacher's trust to learn in their way by discussing and guessing with friends.